Pendidikan Berbasis Nilai untuk Penguatan Integritas dan Antikorupsi Siswa - Putra, Agung Nugraha; Rahmat, Rahmat; Masyitoh, Iim Siti; Fitriasari, Susan (Journal of Civic Education, 2025)
Corruption remains a persistent problem undermining Indonesia’s development at both local and national levels. Addressing this issue requires a holistic strategy, one of which involves integrating values of integrity and anti-corruption into educational practices. Value-Based Education offers an effective preventive approach by providing students with a moral foundation through the internalization of ethical values within contextual and interactive learning experiences. This article employs a literature review method, identifying and analyzing previous research related to integrity, anti-corruption, and value-based education models. The findings highlight nine essential integrity and anti-corruption values: (1) honesty, (2) responsibility, (3) discipline, (4) independence, (5) hard work, (6) simplicity, (7) courage, (8) care, and (9) justice. These values are crucial in guiding students to consistently uphold ethical principles in their daily lives, fostering a culture of integrity and contributing to the creation of a corruption-free society. However, this study is limited by its conceptual nature, as it relies solely on literature review without empirical validation in educational settings. Future research is recommended to conduct experimental or classroom-based studies to assess the practical effectiveness of value-based education models in promoting anti-corruption behavior among students across different educational levels.